Characterisation of human hair keratin fibers - Krishnamoorthy Elavaini Mahaalaxmi (Nanyang Technological University, 2024)
This research investigates interfacial polyelectrolyte complexion (IPC) technique used to form keratin fibers and evaluate the mechanical properties of keratin-based fibers produced by IPC, in relation to its composition and state of hydration. Keratin based polyelectrolyte solutions were extracted from human hair waste using reduction method. The extracted keratin underwent different type of dialysis to form oppositely charged solution. The chitosan based fibers and keratin based fibres were synthesized from these polyelectrolyte solutions. These fibers were then exposed to different rehydration conditions (phosphate buffer, salt solution) upon which the respective change in protein structure and mechanical properties were analysed. The rehydration in phosphate buffer solution has induced beta sheet formation and enhanced the flexibility of the fibers with a significant increase in strain at break value. The strain at break of CK fibers increased from 3.29±1.46% to 30.17±10.20% upon rehydration in PBS. The Young’s Modulus of CK fibers decreased from 1.84±0.76GPa to 0.62±0.39GPa upon rehydration in PBS. This rehydration shows potential to modify mechanical property of keratin-based fibers.